Outcome of scalp reconstruction in a teaching hospital (Bangladesh Medical Journal Khulna, 2016)
An area of loss of scalp could be covered by various methods including local flap, distant flaps, skin graft, free flap surgery or tissue expansion. Each method has some disadvantages, such as postoperative alopecia or donor site morbidities. The study was conducted in the Department of Burn and Plastic Surgery, Khulna Medical College Hospital from July 2011 to June 2015. Scalp reconstruction was performed on 16 patients who sustained scalp loss from RTA, surgery for cancer, burn injuries and machinery injury. The size of the wound ranged from 6 cm2 to 320 cm2. Transposition flap, rotation flap, removal of osteomyelitic bone and skin grafts were done. Among 16 cases, 3 cases (18.75%) were skin grafted, 6 cases (37.5%) were reconstructed with transposition flaps, 5 cases (31.25%) were reconstructed with rotation flap and 2 cases (12.5%) were reconstructed with skin graft after removal of osteomyelitic outer table of skull bone. The postoperative complications seen in this series includes partial graft loss in 2 cases (skin graft), marginal necrosis in 1 case (transposition flap) and alopecia in 11 cases (in skin graft and transposition flap). There was no alopecia in reconstruction with rotation flap. Rotation flaps brings the best outcome in terms of durability and aesthetic acceptability where it is applicable in comparison to other procedure.Bang Med J (Khulna) 2015; 48 : 3-6